Ambulation Support for Reduction of Pain and Uterine Fundal Height in Post-Cesarean (Case Study) - Rusdiana, Meitania; Desmarnita, Ulty (Journal Center of Excellent : Health Assistive Technology, 2024)
Cesarean sections continues to increase globally and now accounts for more than 1 in 5 (21%) of all births. A common problem after a cesarean section is discomfort. One of the discomforts felt after surgery is pain. The pain experienced by post-cesarean mothers is related to two main factors: surgical wounds and uterine contractions. This study aims to describe the effect of implementing ambulation support on pain and the reduction of uterine fundal height post-cesarean. The writing method is a case study. Ambulation support intervention was carried out gradually over 48 hours. After the implementation, the NRS pain scale results decreased from 5 to 3. The WBPRS pain scale decreased from 6 to 3. The uterine fundal height decreased from 12.5 cm to 8 cm, decreasing more rapidly by 4.5 cm on the second day. The results show that ambulation support can help reduce pain and uterine fundal height more quickly. It is hoped that through patient education, accompaniment, and support during ambulation, and supervision during implementation, it can significantly facilitate the recovery of cesarean patients.